Esthetic smile rehabilitation of anterior teeth by treatment with biomimetic restorative materials: a case report - Gouveia TH; Theobaldo JD; Vieira-Junior WF; Lima DA; Aguiar FH (Dove Medical Press, 2017)
Thayla Hellen Nunes Gouveia, Jéssica Dias Theobaldo, Waldemir Francisco Vieira-Junior, Débora Alves Nunes Leite Lima, Flávio Henrique Baggio Aguiar Department of Restorative Dentistry, Piracicaba Dental School, University of Campinas, Campinas, SP, Brazil Background: In daily clinical practice, esthetics of anterior teeth is a common presenting complaint of patients.Objective: This case report discusses the management of asymmetric smile associated with unsatisfactory extensive composite restorations and describes a clinical protocol using the direct composite resin for smile enhancement to restore the dental harmony of anterior teeth.Methods: The treatment planning was based on a diagnostic wax-up and cosmetic mock-up. After clinical and patient approvals were obtained, the patient was subjected to direct and indirect restorative treatment.Conclusion: Nanocomposites are an effective alternative for anterior teeth restorations. Additionally, good planning enables satisfactory esthetic results, leading to the correction of an inappropriate axial inclination of incisors. Keywords: composite, adhesive, smile, esthetic, restoration